Chief human resources officers on top management teams: an empirical analysis of contingency, institutional, and homophily antecedents - Magdalena Abt; Dodo zu Knyphausen-Aufseß (Business Research, 2017)
Having the director of human resources (HR) as a member of the top management team (TMT) and giving him/her the title of chief human resources officer (CHRO) indicates an important strategic and symbolic choice. Such decisions not only determine who participates in controlling an organization and setting its strategic direction, but also reflect the organizational structure. In this paper, we examine the antecedents of CHRO presence according to the contingency, institutional, and homophily theories. Based on a multi-industry sample of 215 firms that considers a 10-year period, we find that the presence of a CHRO is influenced by the rates of unionization, rapid declines or increases in numbers of employees, the employment of a new or outsider chief executive officer (CEO), and the institutionalization of the CHRO position in the industry or firm. However, we find no evidence of the presumed influence of knowledge intensity or the CEO or TMT human resource management (HRM) experience. Overall, we find that the institutional theory has the highest explanatory power regarding the existence of CHRO positions.
Keywords: 650; Chief human resources officer; Top management team; Contingency theory; Institutional theory; Homophily theory; Upper echelon theory